Measurement of physical activity in the pre- and early post-operative period after total knee arthroplasty for Osteoarthritis using a Fitbit Flex device. (January 2018) - Twiggs, Joshua; Salmon, Lucy; Kolos, Elizabeth; Bogue, Emily; Miles, Brad; Roe, Justin
Highlights: Pre- and early post-operative daily step count measured with Fitbit Flex devices for patients with OA undergoing TKA. Pre-operative step count, SF-12 PCS score and BMI were strong correlators with post- operative stepcount. Semi-individualised benchmarks based on correlating scores and grouping are presented. A stepwise multivariate regression model is used to develop a patient specific 6 week step count target. Abstract: Total knee arthroplasty (TKA) is a standard treatment for patients with end stage knee Osteoarthritis (OA) to reduce pain and restore function. The aim of this study was to assess pre- and early post-operative physical activity (PA) with Fitbit Flex devices for patients with OA undergoing TKA and determine any benchmarks for expected post-operative activity. Significant correlations of pre-operative step count, post-operative step count, Body Mass Index (BMI) and Short Form 12 Physical Component Summaries (SF-12 PCS) were found. Mean step counts varied by 3, 203 steps per day between obese and healthy weight patients, and 3, 786 steps per day between those with higher and lower SF-12 PCS scores, suggesting the need for benchmarks for recovery that vary by patient pre-operative factors. A backwards stepwise regression model developed to provide patient specific step count predictions at 6 weeks had an R 2 of 0.754, providing a robust patient specific benchmark for post-operative recovery, while population means from BMI and SF-12 subgroups provide a clinically practical alternative.